Of housewives and feminists: Gender norms and intra-household division of labour - Luise Görges (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2021)
To investigate the role of gender norms in household specialisation choices, I conduct a lab experiment with real hetero-sexual couples playing a battle of the sexes game. The salience of gender norms varies across treatments: the Norm group chooses between strategies labelled as a family specialisation game (Career vs. Family), the Neutral group chooses A vs. B. Women respond strongly to the salience of Norms; they opt for Career at a significantly lower rate compared to Neutral, regardless of familiarity with their partner. By contrast, men's response is weak and heterogeneous across partner and stranger pairings. Additional analyses suggest that the pattern is not explained by differential beliefs, but is consistent with marriage market motives, i.e. some men may want to signal progressive gender attitudes to their partner.
Keywords: D13; J16; J22; 330; experiment; labour division; battle of the sexes; norms; gender